2004
DOI: 10.1073/pnas.0403139101
|View full text |Cite
|
Sign up to set email alerts
|

NFAT5/TonEBP mutant mice define osmotic stress as a critical feature of the lymphoid microenvironment

Abstract: Osmotic stress responses are critical not only to the survival of unicellular organisms but also to the normal function of the mammalian kidney. However, the extent to which cells outside the kidney rely on osmotic stress responses in vivo remains unknown. Nuclear factor of activated T cells 5 (NFAT5)͞tonicity enhancer binding protein (TonEBP), the only known osmosensitive mammalian transcription factor, is expressed most abundantly in the thymus and is induced upon lymphocyte activation. Here we report that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
306
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(322 citation statements)
references
References 29 publications
11
306
2
3
Order By: Relevance
“…Here, the question that needs to be addressed is how high-glucose ambience or hyperglycemia modulates that activity or expression. NFAT5 belongs to the family of transcription factors and is also known as OsREBP or tonicity-responsive-enhancer-binding protein (TonEBP) (28). Upon stimulation by hypertonicity and following phosphorylation, OsREBP and TonEBP rapidly translocate into the nucleus and bind to OsREs in the promoter region of osmoprotective genes to stimulate transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the question that needs to be addressed is how high-glucose ambience or hyperglycemia modulates that activity or expression. NFAT5 belongs to the family of transcription factors and is also known as OsREBP or tonicity-responsive-enhancer-binding protein (TonEBP) (28). Upon stimulation by hypertonicity and following phosphorylation, OsREBP and TonEBP rapidly translocate into the nucleus and bind to OsREs in the promoter region of osmoprotective genes to stimulate transcription.…”
Section: Discussionmentioning
confidence: 99%
“…NFAT5 is also known as OsREbinding protein (OsREBP) or tonicity-responsive-enhancerbinding protein, with consensus sequence of binding motif as: NGGAAAWDHMN (the minimal OsRE motif is underlined) (28). Minimal GGAAA motif was present at six positions in the mouse RSOR 5Ј flanking sequence (Table 1).…”
Section: Isolation Of 5 Flanking Region Of Mouse Rsor and Promoter-acmentioning
confidence: 99%
“…NFAT5 is also necessary for optimal T-cell development in vivo and allows for optimal cell growth ex vivo under conditions associated with osmotic stress [27]. Furthermore, William Go and his co-workers [21,28] measured lymphoid tissue osmolality directly by using a vapor pressure osmometer and they found that in contrast to brain and lung, lymphoid tissues were significantly hypertonic relative to serum. These results suggested that NFAT5, the osmosensitive transcription factor, functions to optimize lymphocyte function in hypertonic lymphoid microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of osmotic stress to the function of T cells or peripheral blood mononuclear cells was first demonstrated in ex vivo studies, showing that proliferation or cytokine production is enhanced upon culture in hypertonic medium [21][22][23]. In T cells, NFAT5 controls the osmotic stress-induced expression of several cytokines, including tumor-necrosis factor, interleukin-2, and lymphotoxin-β [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…NaCl is the main determinant of the extracellular fluid volume of the body and is tightly regulated by pressure receptors, the sympathetic nervous system, and hormones, including the renin-angiotensin-aldosterone system; however, recent studies have demonstrated that isotonicity is not stable in tissues. Lymphoid tissues were found to be hyperosmolar (2), and 23 Na MRI demonstrated greater sodium accumulation in the skin of patients with refractory hypertension (3). Macrophages appear to play a role in buffering excess salt intake, preventing expansion of the extracellular volume and consequently blunting surges in blood pressure.…”
Section: Hsd and Transplant Fatementioning
confidence: 99%